APPLICATION OF THE PBL MODEL WITH THE TaRL APPROACH TO IMPROVE COLLABORATION SKILLS IN THE HUMAN REPRODUCTIVE SYSTEM MATERIAL FOR GRADE VII - Cholifatul Hasanah; Deva Kurniawati; Dita Aurellia Akmal; Dwi Sri Handayani; Faola Firnanda; Farit Nisaussa’adah; Mohammad Budiyanto; Tri Maryono (JPPIPA (Jurnal Penelitian Pendidikan IPA), 2025)
This study aims to find out the impact of applying the Problem-Based Learning (PBL) model with the Teaching at the Right Level (TaRL) approach to improve the collaboration skills and learning outcomes of grade VII-A students at Labschool Junior High School 2 of the State University of Surabaya on the topic of human reproductive systems. The method used is qualitative descriptive, where the researcher describes the students’ collaboration skills and learning outcomes. Students’ collaboration skills increased by 4%, from an average of 83% in cycle I to 87% in cycle II. Peer assessment of collaboration increased by 10%, from 73% in cycle I to 83% in cycle II. Student learning outcomes showed an increase, with the completion criteria rising from 58% in cycle I to 77% in cycle II. These findings demonstrate that the PBL learning model and the TaRL approach are effective in enhancing collaboration skills and student learning outcomes.